Preparation method and application of carbon quantum dot nano-composite coating modified stainless steel bipolar plate

Through the preparation of carbon quantum dot nanocomposite coating modified stainless steel bipolar plates, the problems of easy corrosion and high contact resistance of stainless steel bipolar plates are solved, the stability and output power are improved, and the corrosion resistance and conductivity are achieved. .

CN119265660APending Publication Date: 2025-01-07DALIAN MARITIME UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477680.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Stainless steel bipolar plates are prone to corrosion and have high contact resistance in proton exchange membrane fuel cells and proton exchange membrane water electrolytic cells, resulting in battery failure and power reduction problems.

Method used

The preparation method of modified stainless steel bipolar plates using carbon quantum dot nanocomposite coating is used to build a dense conductive network by combining carbon quantum dots with amorphous carbon plating layer doped with elemental metal niobium, and using the unique solvated structure of carbon quantum dots Promote co-deposition of niobium ions and carbon quantum dots, form a uniform plating layer, reduce contact resistance and improve corrosion resistance.

Benefits of technology

It significantly improves the stability and output power of the bipolar plate, reduces contact resistance, enhances corrosion resistance and mechanical strength, and is suitable for metal bipolar plate substrates with complex runners, and has a simple process and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265660A_ABST
    Figure CN119265660A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a carbon quantum dot nano-composite coating modified stainless steel bipolar plate. The method comprises the following steps: S1, adding carbon quantum dots into a choline chloride-lactic acid-based eutectic solvent containing niobium salt, and carrying out ultrasonic dispersion to obtain a uniform composite electroplating solution; s2, pretreating the stainless steel bipolar plate to obtain a stainless steel bipolar plate to be used; and S3, connecting the stainless steel bipolar plate to be used obtained in the step S2 with the negative electrode of a direct-current electroplating power supply to serve as a cathode, connecting an anode strip with the positive electrode of the direct-current electroplating power supply to serve as an anode, placing the cathode and the anode in the composite electroplating solution obtained in the step S1 in parallel, and performing electrochemical deposition by adopting a constant potential deposition method to obtain the lithium ion battery. The carbon quantum dot nano composite coating modified stainless steel bipolar plate is obtained. The process is simple, the cost is low, the coating is compact and uniform, the electrochemical stability and the conductivity are excellent, and industrial production and application of the bipolar plate for proton exchange membrane fuel cells and proton exchange membrane water electrolysis can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a carbon quantum dot nano-composite coating modified stainless steel bipolar plate, belonging to the field of proton exchange membrane fuel cells and proton exchange membrane water electrolysis. Background Art

[0002] With the shortage of natural resources and the advent of the world energy crisis, sustainable green energy technologies have received increasing attention. Among them, proton exchange membrane fuel cells (PEMFC) and proton exchange membrane water electrolyzers (PEMWE), as the core components of future hydrogen energy systems, are leading the development direction of hydrogen energy technology. These technologies can not only produce hydrogen from renewable energy, but also efficiently utilize hydrogen in the form of electrical energy. Among them, bipolar plates, as key components, not only play an important role in supporting the stack structure, but also are responsible for key functions such as current transmission, reaction gas distribution, and heat transfer. In order to achieve the excellent performance of proton exchange membrane technology and promote its large-scale application, bipolar plates must have excellent corrosion resistance, low contact resistance, good mechanical strength, easy processing, and cost-effectiveness. Although traditional graphite materials are widely used in bipolar plate manufacturing due to their excellent conductivity, their mechanical properties and manufacturing complexity limit their application in large-scale production. Therefore, metal materials such as stainless steel and titanium alloys have received extensive attention and research as alternatives in recent years. However, stainless steel as a bipolar plate material still faces challenges. First, it is easy to passivate in the air, resulting in an increase in the contact resistance between it and the gas diffusion layer, thus affecting the power output of PEMFC / PEMWE. Second, in an acidic environment, although the passivation film can improve its corrosion resistance, it is still difficult to completely avoid corrosion, resulting in a gradual decline in equipment performance.

[0003] In order to overcome the limitations of stainless steel in terms of corrosion resistance and conductivity, researchers have been committed to developing a variety of protective conductive functional coatings in recent years to improve the performance of bipolar plates and enhance the efficiency of PEMFC / PEMWE systems. In particular, amorphous carbon coatings containing a large amount of nanocrystalline structures, among which sp 2 The structure helps to improve the conductivity and wear resistance of the coating, sp 3 The nanostructure enhances the corrosion resistance of the coating, while the nanocrystalline structure improves the mechanical properties of the coating. On this basis, metal doping can not only effectively reduce the residual stress of the coating, but also improve the conductivity and corrosion resistance of the coating. In particular, the use of transition metals with their excellent conductivity and corrosion resistance can construct a metal conductive network, further enhancing the migration speed of electrons in the coating.

[0004] As a new type of nanomaterial, carbon quantum dots (CQDs) exhibit unique physical and chemical properties. When carbon quantum dots are compounded with traditional coating materials, the corrosion resistance and conductivity of the coating can be significantly improved. The small size and high surface area of ​​CQDs enable them to fill the micropores and defects in the coating, forming a tighter protective barrier and reducing the penetration of corrosive media, thereby effectively improving the density and uniformity of the coating. In addition, the chemical stability of carbon quantum dots also helps to improve the durability of the coating in harsh environments and extend the service life of the material. At the same time, CQDs have excellent electrical conductivity. After being compounded into the coating, they can form a conductive network and improve the overall conductivity of the coating. These characteristics make CQDs have broad prospects in coating applications. They can not only significantly improve the performance of coating materials, but also provide new ideas and methods for the development of new functional coatings. In summary, carbon quantum dot composite coatings provide new possibilities for the protection and functional application of materials by improving the corrosion resistance and conductivity of the coating, showing broad application prospects. Summary of the invention

[0005] In order to solve the problems of easy corrosion and high contact resistance of stainless steel bipolar plates in proton exchange membrane fuel cells and proton exchange membrane water electrolyzers in the current technology, which lead to battery failure and power reduction, the present invention provides a preparation method and application of a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate.

[0006] The present invention prepares a nanocomposite coating by composite of zero-dimensional material CQDs, and the composite coating uses amorphous carbon coating doped with single metal niobium as the main film-forming material. Niobium ions in the solution tend to construct a new solvation structure of solvated carbon quantum dot clusters with CQDs, which promotes the co-deposition of niobium ions and CQDs. Among them, CQDs can be used as nucleation centers in situ to induce uniform deposition of the coating on the cathode surface. As the coating continues to be deposited, metal niobium and CQDs are uniformly doped in the amorphous carbon coating, interweaving to construct a dense conductive network, which is conducive to the transmission of electrons. CQDs not only have good conductivity and electrochemical stability, but also their composite coating is conducive to improving the stability and output power of bipolar plates under working conditions. Its structure less than 10nm plays a role in refining grains and uniform coating during the deposition process of the coating. In addition, thanks to the unique solvation structure constructed by CQDs in the electrolyte, it is easier to dissociate than the traditional solvation structure, has a lower desolvation energy, and helps to inhibit the formation of hydrogen evolution reaction and related by-products.

[0007] In order to achieve the above object, the technical solution of the present invention is as follows:

[0008] In one aspect, the present invention provides a method for preparing a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate, the method comprising the following steps:

[0009] S1. adding carbon quantum dots to a choline chloride-lactic acid-based low eutectic solvent containing niobium salt, and ultrasonically dispersing to obtain a uniform composite electroplating solution;

[0010] In S1, the choline chloride-lactic acid-based deep eutectic solvent containing niobium salt is composed of a choline chloride-lactic acid-based deep eutectic solvent prepared from choline chloride and lactic acid in a molar ratio of 1:0.5 to 1:4, 0.01 to 0.05 mol / L niobium pentachloride and 0.1 to 0.5 mol / L citric acid;

[0011] S2, pre-treating the stainless steel bipolar plate to obtain a stainless steel bipolar plate to be used;

[0012] S3. Connect the standby stainless steel bipolar plate obtained in step S2 to the negative electrode of a DC electroplating power source as a cathode, connect the anode sheet to the positive electrode of a DC electroplating power source as an anode, place the cathode and the anode in parallel in the composite electroplating solution obtained in S1, and perform electrochemical deposition by a constant potential deposition method to obtain a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate.

[0013] In the above technical solution, further, in step S1, the preparation method of the carbon quantum dots is:

[0014] 10-15 g of Ketjen black was added to a mixture of 100 mL of concentrated nitric acid and 300 mL of concentrated sulfuric acid, and the mixture was stirred and refluxed at 100 °C for 36 h. After cooling to room temperature, ultrapure water was added to dilute the reaction solution in an ice water bath to make the final volume of the reaction solution about 2 L. The diluted liquid was placed in a dialysis bag with a molecular weight cutoff of 1000 Da, and dialyzed in pure water for about a week, during which the water was changed every 12 h. The dialyzed solution was freeze-dried to obtain carbon quantum dots.

[0015] In the above technical solution, further, in step S1, the method for preparing the composite electroplating solution specifically comprises the following steps:

[0016] S1-1, placing choline chloride and lactic acid in a constant temperature water bath and stirring them in a closed environment until a colorless transparent solution is obtained, the stirring temperature is 40-80° C., and the stirring time is 3-6 hours, to prepare a choline chloride-lactic acid-based low eutectic solvent, and storing it in a constant temperature vacuum box at 70° C. for standby use;

[0017] S1-2, adding niobium pentachloride to a choline chloride-lactic acid-based low eutectic solvent, heating in a constant temperature water bath with stirring for 2 to 5 hours at a stirring temperature of 40 to 80° C. to obtain a milky white solution;

[0018] S1-3, adding 0.1-0.5 mol / L citric acid to the basic electroplating solution obtained in step S1-2, stirring until the citric acid is completely dissolved, to obtain a basic electroplating solution;

[0019] S1-4, adding carbon quantum dots to the basic electroplating solution at a concentration of 0.5-1.5 mg / mL, and ultrasonically dispersing for 0.5-1 h until the carbon quantum dots are completely dispersed in the electroplating solution to obtain a composite electroplating solution.

[0020] In the above technical solution, further, in step S2, the pretreatment process of the stainless steel bipolar plate is:

[0021] The stainless steel bipolar plate was polished and ground with SiC sandpaper of models 400#, 800#, 1200#, and 2000# in turn, rinsed with deionized water, ultrasonically cleaned in acetone solution for 20 minutes, placed in alkaline degreasing solution after cleaning, and soaked for 1 to 10 minutes at 40 to 60° C. for degreasing treatment, cleaned with deionized water, and then soaked in hydrochloric acid pickling solution for 20s to 3min for surface activation, and finally ultrasonically cleaned with deionized water for use.

[0022] In the above technical solution, further, in step S3, the conditions of electrochemical deposition are: deposition potential is -2 to -4 V, composite electroplating solution temperature is 40 to 80° C., and deposition time is 30 to 180 min.

[0023] In the above technical solution, further, in step S3, the anode sheet is a pre-treated niobium sheet;

[0024] The pretreatment process of the niobium plate is as follows: rinse the niobium plate with deionized water to remove surface pollutants, then place the niobium plate in an acetone solution for ultrasonic cleaning for 3 to 5 minutes to remove grease, and finally clean it with deionized water for later use.

[0025] In the above technical solution, further, the carbon quantum dot nanocomposite coating is composed of an amorphous carbon coating doped with elemental niobium and carbon quantum dots, the carbon quantum dots are uniformly distributed in the amorphous carbon coating doped with elemental niobium, and the coating is composed of nanoscale particles.

[0026] Another aspect of the present invention provides an application of a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared by the above method in a proton exchange membrane fuel cell.

[0027] The present invention also provides an application of a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared by the above method in proton exchange membrane water electrolysis.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention uses zero-dimensional material carbon quantum dots to prepare nano-coatings. The niobium ions in the electroplating solution tend to construct a new solvation structure of solvated carbon quantum dot clusters with CQDs, which promotes the co-deposition of niobium ions and CQDs. Among them, CQDs can act as nucleation centers in situ to induce uniform deposition of the coating on the cathode surface, which helps to improve the uniformity of the coating. In addition, thanks to the unique solvation structure constructed by CQDs in the electrolyte, it is easier to dissociate than the traditional solvation structure and has lower desolvation energy, which helps to inhibit the formation of hydrogen evolution reactions and related by-products, reduce coating defects, and improve corrosion resistance.

[0030] 2. CQDs and niobium are evenly distributed in the amorphous carbon coating, interweaving to build a dense conductive network, providing a faster channel for the conduction and transportation of electrons, reducing the contact resistance of the stainless steel bipolar plate, and improving the stability and output power of the bipolar plate under working conditions.

[0031] 3. The present invention adopts an electrochemical deposition method with low cost and simple process. Compared with other bipolar plate modified coating preparation methods, it is more suitable for metal bipolar plate substrates with complex flow channels. The prepared carbon quantum dot nano-composite coating has a coating structure of nano-scale particles, and the coating morphology is dense and uniform, showing superior mechanical strength and stronger corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the present invention is further described in detail below with reference to the accompanying drawings and specific implementation methods.

[0033] Figure 1 This is a scanning electron microscope image of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1, with a scale of 200 nm;

[0034] Figure 2 This is a transmission electron microscope image of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1;

[0035] Figure 3 The potentiodynamic polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1;

[0036] Figure 4 0.6V (vs Ag / AgCl) constant potential polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1;

[0037] Figure 5 The potentiodynamic polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 2;

[0038] Figure 6 The potentiodynamic polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 3;

[0039] Figure 7 This is a contact resistance curve of the stainless steel bipolar plate modified by the carbon quantum dot nanocomposite coating prepared in Example 1. DETAILED DESCRIPTION

[0040] In order to clearly express the purpose and specific implementation scheme of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0042] Example 1

[0043] (1) 15 g of Ketjen black was added to a mixture of 100 mL of concentrated nitric acid and 300 mL of concentrated sulfuric acid, and the mixture was stirred and refluxed at 100 °C for 36 h. After cooling to room temperature, ultrapure water was added to dilute the reaction solution in an ice water bath to make the final volume of the reaction solution about 2 L. The diluted liquid was placed in a dialysis bag with a molecular weight cutoff of 1000 Da, and dialyzed in pure water for about one week, during which the water was changed every 12 h. The dialyzed solution was freeze-dried to obtain carbon quantum dots for use;

[0044] (2) Weighing choline chloride and lactic acid in a molar ratio of 1:2, placing them in a constant temperature water bath environment and stirring them in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 4 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, and the solvent is stored in a constant temperature vacuum box at 70° C. for later use;

[0045] (3) Weighing 0.05 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based deep eutectic solvent, heating and stirring in a constant temperature water bath for 4 hours at a stirring temperature of 70° C., to obtain a milky white solution;

[0046] (4) Weighing 0.5 mol / L citric acid and adding it to a milky white basic electroplating solution of choline chloride-lactic acid-niobium pentachloride, stirring until the citric acid is completely dissolved, to obtain a basic electroplating solution;

[0047] (5) Add the carbon quantum dots obtained in step (1) at a concentration of 0.5 mg / mL to the basic electroplating solution, and ultrasonically disperse for 1 h until the carbon quantum dots are completely dispersed in the electroplating solution to obtain a composite electroplating solution.

[0048] (6) The 316L stainless steel bipolar plate was polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn, rinsed with deionized water, ultrasonically cleaned in acetone solution for 20 minutes, and then placed in alkaline degreasing solution and soaked at 40°C for 5 minutes for degreasing. After cleaning with deionized water, it was soaked in hydrochloric acid pickling solution for 30 seconds for surface activation, and finally ultrasonically cleaned with deionized water for use;

[0049] (7) Rinse the niobium plate with deionized water to remove surface contaminants, then place the niobium plate in an acetone solution for ultrasonic cleaning for 3 minutes to remove grease, and finally rinse it with deionized water for later use;

[0050] (8) The standby stainless steel bipolar plate obtained in step (6) is connected to the negative electrode of a DC electroplating power source as a cathode, and the niobium plate treated in step (7) is connected to the positive electrode of a DC electroplating power source as an anode. The cathode and the anode are placed in parallel in the composite electroplating solution obtained in step (5), and electrochemical deposition is performed by a constant potential deposition method. The deposition potential is -4 V, the composite electroplating solution temperature is 70° C., and the deposition time is 120 min to obtain a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate.

[0051] Figure 1 This is a scanning electron microscope image of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1. It can be seen from the figure that the coating is composed of particles with a size of about 50 nm, which are tightly covered on the 316L stainless steel substrate. The coating is dense and smooth, without obvious defects and holes.

[0052] Figure 2 This is a transmission electron microscope image of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1. The sample was prepared by ultrasonic exfoliation in anhydrous ethanol. Carbon quantum dots with a diameter of less than 10 nm can be observed in the coating fragments, and the interplanar spacing is 0.21 nm, corresponding to the (100) crystal plane of C.

[0053] Example 2

[0054] (1) Add 15 g of Ketjen black to a mixture of 100 mL of concentrated nitric acid and 300 mL of concentrated sulfuric acid, and stir and reflux at 100 °C for 36 h. After cooling to room temperature, add ultrapure water to dilute the reaction solution in an ice-water bath to make the final volume of the reaction solution about 2 L. Place the diluted liquid in a dialysis bag with a molecular weight cutoff of 1000 Da and dialyze it in pure water for about a week, changing the water every 12 hours. Freeze-dry the dialyzed solution to obtain carbon quantum dots for use;

[0055] (2) Weighing choline chloride and lactic acid in a molar ratio of 1:2, placing them in a constant temperature water bath environment and stirring them in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 4 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, and the solvent is stored in a constant temperature vacuum box at 70° C. for later use;

[0056] (3) Weighing 0.05 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based deep eutectic solvent, heating and stirring in a constant temperature water bath for 4 hours at a stirring temperature of 70° C., to obtain a milky white solution;

[0057] (4) Weighing 0.5 mol / L citric acid and adding it to a milky white basic electroplating solution of choline chloride-lactic acid-niobium pentachloride, stirring until the citric acid is completely dissolved, to obtain a basic electroplating solution;

[0058] (5) Add the carbon quantum dots obtained in step (1) at a concentration of 1 mg / mL to the basic electroplating solution, and ultrasonically disperse for 1 h until the carbon quantum dots are completely dispersed in the electroplating solution to obtain a composite electroplating solution.

[0059] (6) The 316L stainless steel bipolar plates were polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn, rinsed with deionized water, and ultrasonically cleaned in acetone solution for 20 minutes. After cleaning, they were placed in alkaline degreasing solution and soaked at 40°C for 5 minutes for degreasing. After cleaning with deionized water, they were soaked in hydrochloric acid pickling solution for 30 seconds for surface activation, and finally ultrasonically cleaned with deionized water for use.

[0060] (7) Rinse the niobium plate with deionized water to remove surface contaminants, then place the niobium plate in an acetone solution for ultrasonic cleaning for 3 minutes to remove grease, and finally rinse it with deionized water for later use.

[0061] (8) The standby stainless steel bipolar plate obtained in step (6) is connected to the negative electrode of a DC electroplating power source as a cathode, and the niobium plate treated in step (7) is connected to the positive electrode of a DC electroplating power source as an anode. The cathode and the anode are placed in parallel in the composite electroplating solution obtained in step (5), and electrochemical deposition is performed by a constant potential deposition method. The deposition potential is -4 V, the composite electroplating solution temperature is 70° C., and the deposition time is 120 min to obtain a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate.

[0062] Example 3

[0063] (1) Add 15 g of Ketjen black to a mixture of 100 mL of concentrated nitric acid and 300 mL of concentrated sulfuric acid, and stir and reflux at 100 °C for 36 h. After cooling to room temperature, add ultrapure water to dilute the reaction solution in an ice-water bath to make the final volume of the reaction solution about 2 L. Place the diluted liquid in a dialysis bag with a molecular weight cutoff of 1000 Da and dialyze it in pure water for about a week, changing the water every 12 hours. Freeze-dry the dialyzed solution to obtain carbon quantum dots for use;

[0064] (2) Weighing choline chloride and lactic acid in a molar ratio of 1:2, placing them in a constant temperature water bath environment and stirring them in a closed manner until a colorless transparent solution is obtained, the stirring temperature is 70° C., the stirring time is 4 h, and a choline chloride-lactic acid-based low eutectic solvent is prepared, and the solvent is stored in a constant temperature vacuum box at 70° C. for later use;

[0065] (3) Weighing 0.05 mol / L niobium pentachloride, adding it to a choline chloride-lactic acid-based deep eutectic solvent, heating and stirring in a constant temperature water bath for 4 hours at a stirring temperature of 70° C., to obtain a milky white solution;

[0066] (4) Weighing 0.5 mol / L citric acid and adding it to a milky white basic electroplating solution of choline chloride-lactic acid-niobium pentachloride, stirring until the citric acid is completely dissolved, to obtain a basic electroplating solution;

[0067] (5) Add the carbon quantum dots obtained in step (1) at a concentration of 1.5 mg / mL to the basic electroplating solution, and ultrasonically disperse for 1 h until the carbon quantum dots are completely dispersed in the electroplating solution to obtain a composite electroplating solution.

[0068] (6) The 316L stainless steel bipolar plates were polished and ground with SiC sandpaper of model 400#, 800#, 1200#, and 2000# in turn, rinsed with deionized water, and ultrasonically cleaned in acetone solution for 20 minutes. After cleaning, they were placed in alkaline degreasing solution and soaked at 40°C for 5 minutes for degreasing. After cleaning with deionized water, they were soaked in hydrochloric acid pickling solution for 30 seconds for surface activation, and finally ultrasonically cleaned with deionized water for use.

[0069] (7) Rinse the niobium plate with deionized water to remove surface contaminants, then place the niobium plate in an acetone solution for ultrasonic cleaning for 3 minutes to remove grease, and finally rinse it with deionized water for later use.

[0070] (8) The standby stainless steel bipolar plate obtained in step (6) is connected to the negative electrode of a DC electroplating power source as a cathode, and the niobium plate treated in step (7) is connected to the positive electrode of a DC electroplating power source as an anode. The cathode and the anode are placed in parallel in the composite electroplating solution obtained in step (5), and electrochemical deposition is performed by a constant potential deposition method. The deposition potential is -4 V, the composite electroplating solution temperature is 70° C., and the deposition time is 120 min to obtain a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate.

[0071] Test Example 1

[0072] Test conditions: The electrolyte was 0.5M H2SO4 and 5ppm HF solution, the reference electrode was Ag / AgCl, the counter electrode was a platinum mesh, the working electrode was the prepared carbon quantum dot nanocomposite coating modified stainless steel bipolar plate, and the test area was 1cm 2 , test temperature 80℃, air passing through the electrolyte.

[0073] Figure 3 The potentiodynamic polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1 of the present invention; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (A cm -2 )). Compared with 316L stainless steel, the stainless steel modified by carbon quantum dot nanocomposite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 A cm -2 Reduced to 8.73×10 -7 A cm -2 .

[0074] Figure 4 0.6V (vs Ag / AgCl) constant potential polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1 of the present invention; the horizontal axis in the figure is time (h), and the vertical axis is current density (A cm -2 The current density of the carbon quantum dot nanocomposite coating remained stable within 24 hours, and the corrosion current density was significantly lower than that of the bare stainless steel plate, indicating that it can effectively protect stainless steel from corrosion under simulated cathode conditions and exhibit excellent electrochemical stability.

[0075] Figure 5 The potentiodynamic polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 2 of the present invention; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (A cm -2)). Compared with 316L stainless steel, the stainless steel modified by carbon quantum dot nanocomposite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 A cm -2 Reduced to 8.12×10 -7 A cm -2 .

[0076] Figure 6 The potentiodynamic polarization curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 3 of the present invention; the abscissa in the figure is the potential (Potential V (vs Ag / AgCl)), and the ordinate is the logarithm of the current density (Log J (A cm -2 )). Compared with 316L stainless steel, the stainless steel modified by carbon quantum dot nanocomposite coating showed better corrosion resistance and more positive corrosion potential. The self-corrosion current increased from 1.66×10 -5 Acm -2 Reduced to 1.12×10 - 6 Acm -2 .

[0077] Test Example 2

[0078] Test conditions: The sample is placed between two gold-plated copper electrodes with the carbon paper used for the fuel cell diffusion layer on both sides as support. A certain pressure is applied on both sides of the copper electrode, and the resistance value under different applied pressures is obtained by recording the current and resistance value under different pressures. The support layer uses the carbon paper used for the fuel cell diffusion layer; the electrode uses a gold-plated metal electrode, generally a gold-plated copper electrode.

[0079] Figure 7 The graph is a contact resistance curve of the carbon quantum dot nanocomposite coating modified stainless steel bipolar plate prepared in Example 1 of the present invention; the horizontal axis in the graph is the applied pressure (Pressure (MPa)), and the vertical axis is the contact resistance (ICR (mΩcm 2 )). As can be seen from the figure, as the pressure increases, the contact resistance first drops sharply, and then slowly drops under high pressure. In the entire pressure range, the contact resistance of the stainless steel modified by the coating is much lower than that of 316L stainless steel.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate, characterized in that: The method comprises the following steps: S1. adding carbon quantum dots into a choline chloride-lactic acid-based low eutectic solvent containing niobium salt, and ultrasonically dispersing the mixture to obtain a uniform composite electroplating solution; In S1, the choline chloride-lactic acid-based deep eutectic solvent containing niobium salt is composed of a choline chloride-lactic acid-based deep eutectic solvent prepared from choline chloride and lactic acid in a molar ratio of 1:0.5 to 1:4, 0.01 to 0.05 mol / L niobium pentachloride and 0.1 to 0.5 mol / L citric acid; S2, pre-treating the stainless steel bipolar plate to obtain a stainless steel bipolar plate to be used; S3. Connect the standby stainless steel bipolar plate obtained in step S2 to the negative electrode of a DC electroplating power source as a cathode, connect the anode sheet to the positive electrode of a DC electroplating power source as an anode, place the cathode and the anode in parallel in the composite electroplating solution obtained in S1, and perform electrochemical deposition by a constant potential deposition method to obtain a carbon quantum dot nanocomposite coating modified stainless steel bipolar plate.

2. The preparation method according to claim 1, characterized in that: In step S1, the method for preparing the carbon quantum dots is: 10-15 g of Ketjen black was added to a mixture of 100 mL of concentrated nitric acid and 300 mL of concentrated sulfuric acid, and the mixture was stirred and refluxed at 100 °C for 36 h. After cooling to room temperature, ultrapure water was added to dilute the reaction solution in an ice water bath to make the final volume of the reaction solution about 2 L. The diluted liquid was placed in a dialysis bag with a molecular weight cutoff of 1000 Da, and dialyzed in pure water for about a week, during which the water was changed every 12 h. The dialyzed solution was freeze-dried to obtain carbon quantum dots.

3. The preparation method according to claim 1, characterized in that: In step S1, the method for preparing the composite electroplating solution specifically comprises the following steps: S1-1, placing choline chloride and lactic acid in a constant temperature water bath and stirring them in a closed environment until a colorless transparent solution is obtained, the stirring temperature is 40-80° C., and the stirring time is 3-6 hours, to prepare a choline chloride-lactic acid-based low eutectic solvent, and storing it in a constant temperature vacuum box at 70° C. for standby use; S1-2, adding niobium pentachloride to a choline chloride-lactic acid-based low eutectic solvent, heating in a constant temperature water bath with stirring for 2 to 5 hours at a stirring temperature of 40 to 80° C. to obtain a milky white solution; S1-3, adding 0.1-0.5 mol / L citric acid to the basic electroplating solution obtained in step S1-2, stirring until the citric acid is completely dissolved, to obtain a basic electroplating solution; S1-4, adding carbon quantum dots to the base electroplating solution at a concentration of 0.5 to 1.5 mg / mL, and ultrasonically dispersing for 0.5 to 1 h until the carbon quantum dots are completely dispersed in the electroplating solution to obtain a composite electroplating solution.

4. The method according to claim 1, characterized in that In step S2, the pretreatment process of the stainless steel bipolar plate is as follows: The stainless steel bipolar plate was polished and ground with SiC sandpaper of models 400#, 800#, 1200#, and 2000# in turn, rinsed with deionized water, ultrasonically cleaned in acetone solution for 20 minutes, placed in alkaline degreasing solution after cleaning, and soaked for 1 to 10 minutes at 40 to 60° C. for degreasing treatment, cleaned with deionized water, and then soaked in hydrochloric acid pickling solution for 20s to 3min for surface activation, and finally ultrasonically cleaned with deionized water for use.

5. The method according to claim 1, characterized in that: In step S3, the conditions for electrochemical deposition are: deposition potential of -2 to -4 V, composite electroplating solution temperature of 40 to 80° C., and deposition time of 30 to 180 min.

6. The method according to claim 1, characterized in that In step S3, the anode sheet is a pre-treated niobium sheet; The pretreatment process of the niobium plate is as follows: rinse the niobium plate with deionized water to remove surface pollutants, then place the niobium plate in an acetone solution for ultrasonic cleaning for 3 to 5 minutes to remove grease, and finally clean it with deionized water for later use.

7. The method according to claim 1, characterized in that The carbon quantum dot nanocomposite coating is composed of an amorphous carbon coating doped with elemental niobium and carbon quantum dots. The carbon quantum dots are evenly distributed in the amorphous carbon coating doped with elemental niobium, and the coating is composed of nano-scale particles.

8. Use of a stainless steel bipolar plate modified by a carbon quantum dot nanocomposite coating prepared by the method according to any one of claims 1 to 7 in a proton exchange membrane fuel cell.

9. Use of a stainless steel bipolar plate modified by a carbon quantum dot nanocomposite coating prepared by the method according to any one of claims 1 to 7 in proton exchange membrane water electrolysis.